2009
DOI: 10.1143/jjap.48.07gm03
|View full text |Cite
|
Sign up to set email alerts
|

Properties of (Bi0.5Na0.5)TiO3–BaTiO3–(Bi0.5Na0.5)(Mn1/3Nb2/3)O3Lead-Free Piezoelectric Ceramics and Its Application to Ultrasonic Cleaner

Abstract: The lead-free piezoelectric ceramics 0.82(Bi 0:5 Na 0:5 )TiO 3 -0.15BaTiO 3 -0.03(Bi 0:5 Na 0:5 )(Mn 1=3 Nb 2=3 )O 3 (abbreviated as BNT-BT-BNMN) was prepared by a conventional process of ceramic engineering. The X-ray diffractometer (XRD) analysis showed that all compositions could form a single perovskite phase. The ceramics showed excellent piezoelectric properties with a coupling factor k t ¼ 41%, a mechanical quality factor Q m ¼ 500, a piezoelectric constant d 33 ¼ 110 pC/N, a relative permittivity " T 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
59
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(63 citation statements)
references
References 14 publications
0
59
0
Order By: Relevance
“…8) Furthermore, the tetragonal side compositions of BNBT have also been important for practical applications such as ultrasonic devices. 31,32) Under this circumstance, there is an urgent demand to know how the quenching treatment works on the BNBT solid solution ceramics even with the tetragonal symmetry and MPB. Therefore, in this study, the quenching effects on piezoelectric properties and depolarization temperatures were experimentally investigated on not only rhombohedral BNLT but also BNBT-based solid solution systems with tetragonal and MPB phases.…”
Section: Introductionmentioning
confidence: 99%
“…8) Furthermore, the tetragonal side compositions of BNBT have also been important for practical applications such as ultrasonic devices. 31,32) Under this circumstance, there is an urgent demand to know how the quenching treatment works on the BNBT solid solution ceramics even with the tetragonal symmetry and MPB. Therefore, in this study, the quenching effects on piezoelectric properties and depolarization temperatures were experimentally investigated on not only rhombohedral BNLT but also BNBT-based solid solution systems with tetragonal and MPB phases.…”
Section: Introductionmentioning
confidence: 99%
“…These materials can be co-sintered with cost-effective nickel electrodes [7], which is not currently achievable for PZT [8]. Tou et al [9] laid the groundwork for hard bismuth-based piezoceramics to be used in ultrasonic cleaners, and Doshida et al [10,11] demonstrated that lead-free piezoceramics have better performance than PZT for high power applications. Recently, a BaTiO 3 (BT)-based solid solution, (1 − x)Ba(Zr 0.2 Ti 0.8 )O 3 -x(Ba 0.7 Ca 0.3 )TiO 3 (BZT-xBCT), has attracted considerable attention due to its promising small and large signal piezoelectric properties [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…First viable contenders and products are now appearing at the marketplace. [3][4][5] However, the properties of most lead-free materials are still lower in comparison to PZT. [6][7][8] Thus, development of lead-free piezoelectric ceramics is of great interest.…”
mentioning
confidence: 99%
“…Therefore, we chose BZT-0.3BCT composition for this study as representative material, which locates deep in the rhombohedral region of the phase diagram. 9,11,12 3 (abbreviated as BZT-0.3BCT) ceramics were synthesized using a conventional solid-state reaction route from oxides and carbonate powders of BaCO 3 (purity 99.8%), ZrO 2 (purity 99.5%), TiO 2 (purity 99.6%), and CaCO 3 (purity 99.5%). Mixed powders were calcined at 1300 C for 2 h and sintered at 1500 C for 2 h. Further information on specimen synthesis can be found elsewhere.…”
mentioning
confidence: 99%